TRENDS IN DEVELOPMENT OF MANAGEMENT ACCOUNTING IN GEORGIA (International Journal of Innovative Technologies in Economy, 2022)
Trends in the development of management accounting in Georgia although the term management accounting has been used around the world since the second half of the 20th century, in Georgia, the scientists have been arguing about the essence of this phenomenon since about the 80s. Is it an independent science? Is it part of science that does not have an independent subject? This is pseudoscience, e.g., such a phenomenon does not exist at all and so on. The dispute is largely due to the reality of accounting science and practice in specific countries. It would be a mistake to think of management accounting as a novelty for the domestic economy. The accountant of that time was engaged both in accounting and in planning and analytical work. Along with the development of the socialist economic system in the country and the strengthening of central planning, there was a gradual separation from the Accounting Service of the Planning and Financial Departments, with the transfer of part of the accounting authority to them. As a result, the activities of the accountant were actually reduced to the accounting of the facts of the economic life of the enterprise. As a result, the activities of the accountant were actually reduced to the accounting of the facts of the economic life of the enterprise. Thus, summarizing the issues discussed above, it should be noted that management accounting - is an integrated system of cost accounting and revenue, valuation, planning, monitoring, and analysis which systematizes information for operational management decisions. The existing organizational structure of the enterprise should be regularly reviewed and revised to reflect the changes occurring in the economic activity (production of new products, technological change, change management, etc.), and the achievements of scientific and technological progress. In improving the organizational structure of enterprises, it is important to properly change the approaches to the preparation of internal reporting and performance assessment.